2023
DOI: 10.1186/s13071-022-05579-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the diversity, host preferences and infectivity of mosquitoes in two arbovirus-endemic regions of Costa Rica

Abstract: Background Mosquitoes are vectors of various arboviruses belonging to the genera Alphavirus and Flavivirus, and Costa Rica is endemic to several of them. The aim of this study was to describe and analyze the community structure of such vectors in Costa Rica. Methods Sampling was performed in two different coastal locations of Costa Rica with evidence of arboviral activity during rainy and dry seasons. Encephalitis vector surveillance traps, CDC fem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
2
1
Order By: Relevance
“…Contrary to some previous studies that reported changes in virome composition according to the collection season [ 63 , 64 ], we did not observe such an association in Cambodian mosquitoes. This absence of difference can be explained by the fact that the presence of mosquito larval habitats harboring these viruses may not depend on seasonal precipitation and can persist throughout the year.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to some previous studies that reported changes in virome composition according to the collection season [ 63 , 64 ], we did not observe such an association in Cambodian mosquitoes. This absence of difference can be explained by the fact that the presence of mosquito larval habitats harboring these viruses may not depend on seasonal precipitation and can persist throughout the year.…”
Section: Discussioncontrasting
confidence: 99%
“…However, further research is needed to understand how tree cover management could be applied for such public health protections. For example, future studies should aim to capture the seasonality of vector presence and abundance along tree cover gradients (Calderón-Arguedas et al ., 2008; Troyo et al ., 2008; Romero-Vega et al ., 2023); assess relationships between vector presence and other factors in habitats that have similar tree cover but differ in aspects such as crop type or tree cover geometry; and use reforestation efforts or experimental tree cover additions at relevant spatial scales to test mosquito community responses. In the study region, tree cover responses of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Shannon's diversity index (SI) is commonly used in ecology to represent the diversity and richness of different species [29]. Recently, this index has been used to analyze the mosquito species diversity and West Nile virus transmission in Costa Rica [30]. Therefore, our study uses this idea to investigate the effect of LULC diversity on the spatial patterns of dengue infection.…”
Section: Landscape-level Variablesmentioning
confidence: 99%